Sistem Perkawinan Sesama Suku Menurut Hukum Adat Leworook di Desa Leraboleng Kecamatan Titehena Kabupaten Flores Timur - Ignasius Lawe Makin; Agustinus Hedewata; Husni Kusuma Dinata (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to the same-tribe marriage system according to leworook customary law in Leraboleng Village, Titehena Sub-district, East Flores Regency. This research is an empirical research, with field data as the main source of data such as interviews and observations. The results of the research that has been conducted, obtained that: (1) The Leworook community adheres to a three-stove marriage system with a patrilineal kinship system or kinship according to the father's line. the Leworook customary community's marriage system also adheres to exogamy marriage where a boy is obliged to marry a woman outside his tribe or clan. The marriage system between tribes means that the tribes in the Leworook indigenous community are grouped into three clans. (2) The marriage system according to Leworook customary law has an interconnected system between one tribe and another, stages of marriage that are highly respected in order to avoid inbreeding with other tribal groups and rules that need to be maintained and should not be violated.